Profil Glukagon Tikus Diabetik Dengan Perlakuan Ekstrak Daun A.Altilis Dan GABA - Meti Indrowati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Glucagon, along with insulin, is a hormone that has close relationship with diabetes in term of maintaining glucose homeostasis. Glucagon is a peptide hormone that is synthesized from 29 amino acid and released by alfa pancreatic cells. Glucagon production and secretion are important mechanism to prevent hypoglycemia by triggering glycogenolysis and gluconeogenesis in carbohydrate metabolism.  The aim of study is to knowing the effect of ethanolic extract of A.altilis leaves and GABA on serum glucagon profile of diabetic rats.This study was done by using  Completely Randomized Design and male Sprague Dewley rats. The rats were devided into normal control group and diabetic rats groups. Levels of serum glucagon  were measured in days 7 and 42 tratments with ELISA Enzyme Linked Immunosorbent Assay method. Quantitative data were  analyzed using ANOVA at 95% confidence level.  The result indicated that 50 mg kg-1 bw  GABA, 400 mg kg-1bw  and 800 mg kg-1 bw  ethanolic extract of A. altilis leaves increased the serum glucagon level. Glucagon profile shows the highest percentage of  serum glucagon elevation  in the 800 mg kg-1 bw  ethanolic extract of A. altilis leaves group treatment. The result of the study expected to be one of scientific information that supports further research related to the use of GABA in natural ingredients as antidiabetes.